Screening, Recruitment, and Baseline Characteristics for the Strategies to Reduce Injuries and Develop Confidence in Elders (STRIDE) Study. (17th July 2018) - Gill, Thomas M; McGloin, Joanne M; Latham, Nancy K; Charpentier, Peter A; Araujo, Katy L; Skokos, Eleni A; Lu, Charles; Shelton, Amy; Bhasin, Shalender; Bianco, Luanne M; Carnie, Martha B; Covinsky, Kenneth E; et al.
Abstract: Background: We describe the recruitment of participants for Strategies to Reduce Injuries and Develop Confidence in Elders (STRIDE), a large pragmatic cluster randomized trial that is testing the effectiveness of a multifactorial intervention to prevent serious fall injuries. Eligible persons were 70 years or older, community-living, and at increased risk for serious fall injuries. The modified goal was to recruit 5, 322 participants over 20 months from 86 primary care practices within 10 diverse health care systems across the United States. Methods: The at-risk population was identified using two distinct but complementary screening strategies that included three questions administered centrally via the mail (nine sites) or in the clinic (one site), while recruitment was completed centrally by staff at Yale. Results: For central screening, 226, 603 letters mailed to 135, 118 patients yielded 28, 719 positive screens (12.7% of those mailed and 46.5% of the 61, 729 returned). In the clinic, 22, 537 screens were completed, leading to 5, 732 positive screens (25.4%). Of the 34, 451 patients who screened positive for high risk of serious fall injuries, 31, 872 were sent a recruitment packet and, of these, 5, 451 (17.1%) were enrolled over 20 months (mean age: 80 years; 62% female). The participation rate was 34.0% among eligible patients. The enrollment yields were 3.6% (vs 5% projected) for each patient screened centrally, despite multiple screens, and 10.5% (vs 33.9% projected) for each positive clinic screen. Conclusions: Despite lower-than-expected yields, the STRIDE Study exceeded its modified recruitment goal. If the STRIDE intervention is found to be effective, the two distinct strategies for identifying a high-risk population of older persons could be implemented by most health care systems.